Translating nature terminology - Kasprzak, Wojciech (Cambridge Scholars, 2011)
Translating Nature Terminology hopes to fill a vacuum in the market, combining practical advice for translators with aspects of linguistics and natural sciences. It is a response to the growing popularity of bilingual (Polish-English) publications on natu.